Semantic Dimensions of Menu Naming in Arabic Cuisine Merchants on GoFood: A Socio-Onomastic Study - Mokhamad Azis Aji Abdilah; Ela Agestina (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
The naming of Arabic-language foods on digital platforms, such as GoFood, serves not only as a product label but also conveys complex social, cultural, and semantic meanings. This study examines the socio-onomastic ang semantic aspects of Arabic food names and how they reflect cultural identity, historical heritage, and social symbolism. Using a qualitative descriptive approach with content analysis, data were collected from food menus featuring Arabic elements in their names. Examples of analyzed names include Umm Ali, Kabsa Madinah, Sheikh Tea, Siti Mandhi, and Adhani Tea Moci, which illustrate naming practices that convey origins, personal or historical references, and associative meanings such as luxury, religiosity, or modern fusion. The findings reveal that these names are carefully chosen to communicate cultural authenticity, evoke emotional and social associations, and enhance consumer perception. Overall, the study highlights how socio-onomastic strategies in digital food naming function as a tool for branding, cultural representation, and market positioning in the contemporary culinary industry.